Standardized Rhodiola rosea injection for left ventricular remodeling and inflammation in patients with HFrEF: a systematic review and meta-analysis - Du, Xuqin; Wang, Xiaorong; Zhang, Ruodai; Chen, Yong; Chen, Qian; Yao, Jing; Shi, Lipeng; Ren, Yi (Frontiers in Pharmacology, 2025)
BackgroundHeart failure with reduced ejection fraction (HFrEF) affects a substantial portion of the global population, with left ventricular remodeling (LVR) and inflammation identified as key contributors to disease progression. Standardized Rhodiola rosea Injection (SRRI) is a pharmacopoeia-based botanical drug preparation derived from Rhodiola rosea, widely used in China for heart failure treatment. It is standardized in composition and quality control, with known antioxidant, anti-inflammatory, and anti-fibrotic properties. However, comprehensive evaluations of SRRI’s effects on LVR and inflammatory mediators in HFrEF patients are limited.PurposeTo evaluate the effects of SRRI on LVR and inflammatory mediators in patients with HFrEF.MethodsA systematic review and meta-analysis were conducted following PRISMA and Cochrane guidelines. Eight databases were searched for randomized controlled trials (RCTs) on SRRI in HFrEF treatment with studies identified from inception to 31 October 2024. Quality assessment of the included studies was conducted using the Cochrane Collaboration’s risk of bias tool and the modified Jadad scale. Statistical analysis was performed using Stata version 17.0, with sensitivity analyses conducted by sequentially excluding studies to assess the robustness of findings. Publication bias was evaluated using Egger’s test.ResultsTwenty-five RCTs with 2,325 participants were included. SRRI significantly improved LVR, indicated by increased LVEF (MD = 6.81, 95% CI: 5.71 to 7.91, P < 0.00001), reduced LVEDD (MD = −4.37, 95% CI: −5.42 to −3.33, P < 0.00001), and decreased LVESD (MD = −4.48, 95% CI: −5.42 to −3.58, P < 0.00001). Additionally, SRRI effectively reduced inflammatory mediators, including TNF-α (MD = −10.37, 95% CI: −12.96 to −7.78, P < 0.00001), IL-6 (MD = −6.99, 95% CI: −8.88 to −5.11, P < 0.00001), and hs-CRP (MD = −2.58, 95% CI: −3.37 to −1.79, P < 0.00001). SRRI also significantly reduced BNP (MD = −105.10, 95% CI: −132.29 to −77.90, P < 0.00001) and NT-pro BNP (MD = −415.95, 95% CI: −553.00 to −278.89, P < 0.00001). Clinical effectiveness was improved, with no significant increase in adverse reactions (RR = 0.86, 95% CI: 0.59 to 1.25, P = 0.44). Sensitivity analyses confirmed the robustness of these findings, and no significant publication bias was detected.ConclusionSRRI appears to effectively enhance LVR, reduce inflammatory mediators, and improve clinical effectiveness in HFrEF patients while maintaining a favorable safety profile. However, the current evidence is limited by methodological shortcomings, and further well-designed, multicenter RCTs are needed to validate these findings, especially in diverse populations and over long-term treatment durations.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=603884, Identifier CRD42024603884.